A microcontroller-based recloser implementation for the UP-PSSL power system simulator - Cardona, Niccolo Andrew B.
High voltage reclosers are expensive and bulky for use in power system micro-hardware simulations. The project aims to construct a compact and low-cost alternative recloser implementation for the Terco PST2200 Power System Simulator currently used in the Power System Simulation Laboratory (PSSL). The researchers implemented a scaled-down version of a high voltage recloser using a Zilog Z8F6421 microcontroller. It is dedicated for the data acquisition, control, and communications of the device. The recloser consists of a signal conditioning circuit, a data acquisition module, and a controller. A Human-Machine Interface (HMI) and a Graphical User Interface (GUI) were also developed to allow manual or remote control of the device and for the configuration of the recloser relay settings. The design, capabilities and features of this recloser implementation mimics that of an actual recloser. It is capable of detecting and interrupting fault currents and automatically recloses according to the recloser operations set by the user. The device bases its fault current interrupting time from a user-selected standard time-current characteristic (TCC) curve whose equations are stored in the microcontroller's internal memory.